All together passionately. Skiing holidays at family hotels - Giannitrapani, Alice (E|C, 2020)
Family hotels are accommodation facilities designed for families with children. They present super-safe playrooms and entertainment services, swimming pools, restaurants and wellness centers. They promote themselves as idyllic places for adults and children. They promise freedom and happyness for all members of the family. We will analyse the organisation of spaces and times of this structures pointing out the strictly codified discplinary sistemt that stands behind this perfect organisation.